The impact of oil on the economic situation in Iraq 1918-1945 - Fawaz Hamad Mahmmod (مجلة جامعة الأنبار للعلوم الإنسانية, 2020)
The oil policy of the Iraqi government after 1921 was characterized by confusion, confusion, and lack of clarity. The foreign oil company controlled Iraqi oil through the sharing of Iraqi oil between the governments of Western countries through what was given to it by the San Remo conference in 1920.Where the Turkish Oil Company got a percentage ranging from (23.75%), the French Oil Company (23.75%), Shell (British-Dutch), a percentage of (23.75%), and Aramco Company (23.25%), and each entity got a percentage (5%) .Thus, the Western countries and their oil companies, whose name was changed in 1929, shared to the Iraq Petroleum Company, and thus Iraq lost control of its oil imports and its resources became in the hands of foreign companies. And it continued to serve the interests of Western countries, forgetting the right of the Iraqi people, who were in dire need of oil imports at the time when the Iraqis only received cheap prices that did not meet their national economy and their cables with heavy restrictions for long periods that extended to less than seventy-five years